Capillary Blood Glucose and Venous Blood Glucose Measured with Portable Digital Glucometer in Diabetic Dogs - Borin, Sofia; Crivelenti, Leandro Zuccolotto; Rondelli, Mariana Cristina Hoeppner; Tinucci-Costa, Mirela (Brazilian Journal of Veterinary Pathology, 2012)
This study aimed to compare the glycemic values obtained with a glucometer with those determined by a colorimetric enzymatic assay in venous blood as well as to evaluate the possibility of using capillary blood samples of dogs with diabetes mellitus. A group with 30 diabetic dogs was formed and from each dog three blood samples were obtained for glycemic evaluations by different methods and blood collection sites. The mean glycemic values showed no significant difference between the different sites of blood collection and methods (P=0.90). Venous, pinna and carpal pad blood glucose showed excellent correlation with the colorimetric enzymatic assay (r=0.98; r=0.95 and r=0.96 respectively) and the obtained values fit properly the clinically acceptable intervals in the error grid analysis. The present study revealed that carpal pad, venous and pinna glucose measurements are clinically acceptable and this method is feasible for use in hospitalized diabetic dogs. The sample attainment of carpal pad proved to be effective and a viable alternative. Further work is necessary to assess the utility of this technique in a home environment.